Solitary Metastasis in the Mediastinal Lymph Node After Radical Nephrectomy for Clear Cell Renal Cell Carcinoma: A Case Report and Literature Review - Lin, Hang; Zhang, Heng; Cheng, Yuanda; Zhang, Chunfang (Frontiers in Oncology, 2020)
Background: Renal cell carcinoma can metastasize to virtually any anatomical site throughout the body, especially the lung, bone, lymph nodes, liver, and brain. However, it is extremely rare for renal cell carcinoma to metastasize solely to the mediastinal lymph node more than 15 years after radical nephrectomy. Case presentation: The case we present here is that of a 50-year-old Chinese male with an isolated posterior mediastinal lymph node metastasis of clear cell renal cell carcinoma 16 years after radical nephrectomy. However, based on imaging examination, the mass was clinically misdiagnosed as Castleman's disease before operation. Following surgical excision of the mass, it was finally judged to be a metastasis from clear cell renal cell carcinoma according to the patient’s medical history and immunohistochemical findings. Currently, there is no clinical or radiological finding the recurrence of metastasis after 10 months of follow-up. Conclusion: We report a case of solitary metastasis in the posterior mediastinal lymph node 16 years after radical nephrectomy for clear cell renal cell carcinoma. Given the long disease-free interval between primary renal cell carcinoma to isolated mediastinal lymph node metastasis, it is important to conduct a lifelong regular follow-up, including thoracic computed tomography. In addition, surgical resection remains the best method of treatment for mediastinal lymph node metastases from clear cell renal cell carcinoma if the metastatic lesion is limited.